Characterization The Flavonoids Extract of Tridax Procumbens l. Leaves and Betel Lime as Materials for Open Wound Analgesic Ointment - Zainullah, Muhammad; Setiana, Mina Devika; Fatimah, Vera Nur; Fitriana, Ilma; Kurniawan, Robi (International Journal of Applied Sciences and Smart Technologies, 2024)
Tridax procumbens L. has quite high flavonoid content (6.51%). Flavonoids have antimicrobial effects that can fight bacteria. Besides that, the flavonoid content of T. procumbens leaves as an analgesic inhibits has the potential to be used as an analgesic ointment material for open wounds. Betel lime (CaCO3) also helps speed up the healing of open wounds. This research aims to optimize a mixture of T. procumbens leaves and betel lime to make a material-based herbal ointment that effective in healing open wounds. This research uses quantitative and qualitative approaches. The dependent variables used are the results of FTIR characterization, SEM-EDX, and antibacterial tests. Research results show that the 1:1 ointment sample has the highest homogeneity with an average particle size distribution of 11.95 nm. The weight and total atomic weight of carbon and calcium elements fluctuated with increasing leaf extract concentration, but the 2:1 ointment sample showed a higher calcium element content than the other samples because the amount of whiting was greater than the leaf extract. Flavonoid functional groups were successfully detected, O-H, C-H, and C-O-C. In S. aureus, it was shown that the 1:1 ointment sample was able to inhibit bacterial growth with an inhibition zone diameter of 0.062 to 1.510 cm. In addition, the contents of stigmasterol, β-sitosterol, and n-hexadecanoid acid are the main components that play a role in the inhibitory activity of bacteria. Keywords: Analgesic ointment, flavonoids, open wounds